Analisis Praktek Bagi Hasil Dalam Peningkatan Kesejahteraan Petani Karet di Desa Siantona Kecamatan Lembah Sorik Merapi Kabupaten Mandailing Natal - Zulpan, Zulpan; Angraini, Tuti; Syarvina, Wahyu (Journal of Computer Science and Information System(JCoInS), 2024)
Cooperation in agriculture one of them Mukhabarah is a contract of cooperation in agriculture or plantation between landowners and tenants, where landowners will hand over a piece of land to tenants who are willing to provide seeds and manage the land, the results of which will be divided in accordance with the agreement. This study itself aims to find answers to the main issues of how the mechanism of implementation of the plantation management cooperation agreement that applies in the community Sorik Marapi Valley subdistrict Mandailing Natal and how the review of Islamic law on the practice of community plantation management cooperation in the village of siantona sorik Valley subdistrict Marapi Mandailing Natal reviewed according to the concept of mukhabarah. To achieve the objectives of the study, the authors used descriptive method of analysis through primary data obtained from field research (field research) and secondary data obtained from library research (library research). The results showed that the practice of the community in the District of Lembah Sorik Marapi Mandailing Natal Regency is a system of cooperation there is injustice where the people of Siantona Village is still using Customs since ancient times but in practice it is not fully in accordance with the concept taught by Islam, because of the division of results between the parties that cause the imbalance of division between owners and managers, which resulted in the position of managers to be stronger than the landowners themselves. Although in the community this is considered fair and is common in the community, but in terms of Islamic law it is not allowed. Therefore, it is considered necessary to negotiate between parties who work together to make an agreement that is balanced, fair and also in accordance with what is allowed in Islam.